UTILIZATION OF AC WATER AS AN ALTERNATIVE WATER RESOURCE FOR INCLUSIVE AND SUSTAINABLE GREEN ECONOMIC DEVELOPMENT - Nababan, Benny Osta; Dewita Sari, Yesi; Anwar, Syaiful; Kusumawati, Rini; Mujito, Mujito; Mausuli, Silma; Saripah, Mutiara Silvia; Dwianto, Rusli; Darma Cintia, I Gusti Ayu (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The Anugerah Insani Foundation oversees several schools, including kindergarten, elementary school, middle school and high school, which requires a lot of water resources every day. So far, water resources have only relied on groundwater for ablutions, toilets, watering plants and cleaning. In the dry season, water availability at this school becomes a problem because the groundwater dries up. Finally, the limited water supply does not match the needs of the school. In September 2023, the toilets at the school ran dry so there was no water, so they had to connect pipes from other places while waiting for groundwater drilling to a depth of 30-40 meters. To meet the limited water resources, a collective of AC wastewater was built through pipes and collected into the tornado. The resulting conclusion is that AC waste water can be used as an alternative for school water needs which can be used for watering plants and cleaning the school. The results of the FGD with the government regarding halalness and certainty of the required water quality standards. For uses related to physical members, both for ablution, washing hands and toilets, the school cannot use them because there must be a halal test and hygiene test decided by the government. The next suggestion is to ensure that there are regulations for AC wastewater related to halal testing and hygiene testing by the government.